2014
DOI: 10.1093/nar/gku1164
|View full text |Cite
|
Sign up to set email alerts
|

GenoBase: comprehensive resource database of Escherichia coli K-12

Abstract: Comprehensive experimental resources, such as ORFeome clone libraries and deletion mutant collections, are fundamental tools for elucidation of gene function. Data sets by omics analysis using these resources provide key information for functional analysis, modeling and simulation both in individual and systematic approaches. With the long-term goal of complete understanding of a cell, we have over the past decade created a variety of clone and mutant sets for functional genomics studies of Escherichia coli K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 51 publications
(60 reference statements)
0
47
0
Order By: Relevance
“…Notably, it provides a phenotype for 283 genes of uncharacterized function (out of 1,306 y‐genes). The Keio collection, as any genomewide deletion collection (Teng et al , ), is no stranger to gene duplications and compensatory mutations (Yamamoto et al , ; Otsuka et al , ). Although their occurrence can impact interpretation at the gene level, “suppressor” mutants tend to display more WT‐like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it provides a phenotype for 283 genes of uncharacterized function (out of 1,306 y‐genes). The Keio collection, as any genomewide deletion collection (Teng et al , ), is no stranger to gene duplications and compensatory mutations (Yamamoto et al , ; Otsuka et al , ). Although their occurrence can impact interpretation at the gene level, “suppressor” mutants tend to display more WT‐like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it provides a phenotype for 283 genes of uncharacterized function (out of 1306 y-genes). The Keio collection, as any genome-wide deletion collection (Teng et al, 2013), is no stranger to gene duplications and compensatory mutations (Otsuka et al, 2015;Yamamoto et al, 2009). Although their occurrence can impact interpretation at the gene level, "suppressor" mutants tend to display more WT-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Cells expressing this protein showed a nonhomogeneous distribution of fluorescence throughout the cell volume, with visible puncta of more intense fluorescence (data not shown). Previous work has similarly shown that fusion of Dps with the green fluorescent protein (GFP) resulted in aggregation of this fusion protein in E. coli cells (44). This strain was therefore excluded from further experimentation.…”
Section: Construction Of a Reporter Strain For Dps Productionmentioning
confidence: 99%